(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
This study investigated the level and occurrence of 13 organophosphorus pesticides (OPPs) residues in cocoa beans from some cocoa farms in Ekiti state, Nigeria. The pesticides in the cocoa beans were extracted and cleaned up on silica gel adsorbent. A gas chromatograph coupled with flame photometric detector (FPD) was used to quantify the pesticides. The reliability of the analytical method was examined by spiking the beans with known concentration of the pesticides and analysed following similar procedure of extraction and clean-up. The percentage of pesticides recovered ranged from 88% to 92%. Dichlorvos, mevinfos, diazinon, chlorpyrifos, dimethoate and parathion were detected with varying concentration in the bean samples whilst phosphamidon, pirimiphos-methyl, fenthion, bromophos, isofenfos, diclofenthion and ethion showed no detectable level. The concentration of OPPs ranged from ND - 58μg/kg and ND - 85μg/kg for the dry and wet seasons respectively. Analysis of variance (ANOVA) showed no significant variation (p ˃ 0.05) in the levels of all detectable pesticides among the sampled farms whilst dichlorvos, diazinon, dimethoate and chlorpyrifos showed significant difference between both seasons. Residual levels of these detectable pesticides were below the maximum residue limits (MRLs) set by the European Union in food. Hence, the cocoa beans from the study areas are considered safe for consumption. Bangladesh J. Sci. Ind. Res. 52(4), 281-288, 2017